Increased activated memory B-cells in the peripheral blood of patients with erythema nodosum leprosum reactions. - Edessa Negera; Stephen L Walker; Yonas Bekele; Hazel M Dockrell; Diana N Lockwood (Public Library of Science (PLoS), 2017)
B-cells, in addition to antibody secretion, have emerged increasingly as effector and immunoregulatory cells in several chronic inflammatory diseases. Although Erythema Nodosum Leprosum (ENL) is an inflammatory complication of leprosy, the role of B- cell subsets has never been studied in this patient group. Therefore, it would be interesting to examine the contribution of B-cells in the pathogenesis of ENL. A case-control study design was used to recruit 30 untreated patients with ENL and 30 non-reactional lepromatous leprosy (LL) patient controls at ALERT Hospital, Ethiopia. Peripheral blood samples were obtained before, during and after treatment from each patient. Peripheral blood mononuclear cells (PBMCs) were isolated and used for immunophenotyping of B- cell subsets by flow cytometry. The kinetics of B-cells in patients with ENL before, during and after Prednisolone treatment of ENL was compared with LL patient controls as well as within ENL group. Total B-cells, mature B-cells and resting memory B-cells were not significantly different between patients with ENL reactions and LL controls before treatment. Interestingly, while the percentage of naive B-cells was significantly lower in untreated ENL patients than in LL patient controls, the percentage of activated memory B-cells was significantly higher in these untreated ENL patients than in LL controls. On the other hand, the percentage of tissue-like memory B-cells was considerably low in untreated ENL patients compared to LL controls. It appears that the lower frequency of tissue-like memory B-cells in untreated ENL could promote the B-cell/T-cell interaction in these patients through downregulation of inhibitory molecules unlike in LL patients. Conversely, the increased production of activated memory B-cells in ENL patients could imply the scale up of immune activation through antigen presentation to T-cells. However, the generation and differential function of these memory B-cells need further investigation. The finding of increased percentage of activated memory B-cells in untreated patients with ENL reactions suggests the association of these cells with the ENL pathology. The mechanism by which inflammatory reactions like ENL affecting these memory cells and contributing to the disease pathology is an interesting area to be explored for and could lead to the development of novel and highly efficacious drug for ENL treatment.